A Mobile Application Penyikang Applied in Postpartum Pelvic Floor Dysfunction: A Cross-Sectional Study to Analyze the Factors Influencing Postpartum Pelvic Floor Muscle Strength and Women's Participation in Treatment. (28th July 2020) - Li, Juan; Sun, Xiaoyan; Wang, Congyu; Zhang, Zujuan; Xie, Zhenwei
Abstract : Objectives . Postpartum pelvic floor muscle (PFM) injuries are the result of pregnancy and delivery, which lead to a series of symptoms requiring long-term follow-up. Mobile health platforms are progressively used for monitoring clinical conditions in medical subjects. This survey was a cross-sectional design based on collecting data from an application (Penyikang). We retrospectively analyzed the risk factors for weak postpartum PFM and further analyzed the factors influencing women's participation in the treatment which may help to improve the app's application in the future. Methods . We enrolled postpartum women who gave birth at the Women's Hospital, Zhejiang University School of Medicine from August to November 2017; trained them to use the app; and collected the demographic and clinical information. This app requires users to fill questionnaires to assess their knowledge of pelvic floor dysfunction (PFD) and pelvic floor muscle training (PFMT) and experience with PFMT, and each therapy evaluation was restored. The relationship between the knowledge of PFMT/PFD, UI symptoms, and PFM strength was analyzed. Cluster analysis was used to define the degree of participation and identify the factors influencing the patients' participation in intensive therapy and evaluation. Results . 1982 postpartum women who enrolled in the app program were defined as weak PFM. Younger maternal age, cesarean section, and without delivery injury were found as the prognostic factors to PFM strength (both type I and type II muscle fibers) (P < 0.05 ), and higher educational level was also in favor of type II muscle fibers (P < 0.05 ). Patient-reported UI symptoms were associated with weak PFM strength (P < 0.05 ); there were no significant differences between knowledge of PFMT or PDF and PFM strength. Finally, patients with a higher degree of participation were more likely to accept the treatment (P < 0.05 ). Conclusions . The mobile app provides a new applicative way to investigate postpartum PFD. The factors influencing women's participation can help us focus on strategies to increase the patients' compliance, and then we will apply the app into more areas to improve the prevention and treatment of postpartum PFD.